Answer:
-11
Step-by-step explanation:
Our function is 2x-13x+5
- 2x-13x+5= -11x+5
- F(0)= 5 and F(6)= -11*6+5 = -61
- let m be the average change : m= (-61-5)/6= -11
Answer:
30in squared
Step-by-step explanation:
(4x5) + ((4x3)/2) + ((4x2)/2) = 20 in sq.
(a) 34 copies
4520 = 1800 + 80c
2720 = 80c
34 = c
(b) $3,720
P = 1800 + 80(24)
P = 1800 + 1920
P = 3720
Let me know if you have questions about this
Answer:
s = 14
Step-by-step explanation:
Step 1: Combine like terms.
Step 2: Multiply both sides by 2/3.
70000000 the reason that this is the answer to this is because if multiply 10 by 7 you will have 70 and just add 6 zeros